Kajian Hermeneutik Ulangan 22:13-30 dalam Konteks Kesadaran Jemaat Kristen Masa Kini terhadap Pernikahan Dini - Prasandi Prasandi; Yana Maharani; Yogi Parinding; Mega Tri Palimbong; Bunga Lestari (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
This study aims to examine Deuteronomy 22:13-30 using a hermeneutic approach and relate it to the current level of awareness of early marriage among Christian congregations. The method used was a qualitative literature study, with the Bible as the primary source, supplemented by various related theological literature. The results indicate that this section of the text contains important theological values, such as holiness, justice, responsibility, and respect for human dignity, especially women, in the context of marriage. Although this text originates from the patriarchal culture of ancient Israel, its principles remain relevant in today's context. Regarding the phenomenon of early marriage, it was found that this practice often occurs without adequate preparation, whether emotional, spiritual, or economic, and thus risks causing various problems in the household. Therefore, the church has a responsibility to raise congregational awareness through faith formation, premarital education, and contextual pastoral care. This study confirms that marriage is a life calling that requires maturity and serious commitment, not simply a solution to social problems.